I got the 2 obvious answers I think:
x(x + 1)^3 - 42(x + 1)^2 = 0
x(x + 1)^3 = 42(x + 1)^2
x(x + 1) = 42
(x + 1/2)^2 = 169/4
x + 1/2 = +- 13/2
x = 6, x = -7
This is my work so far, and the book says I'm correct. However there is an additional answer x = -1, and I don't understand where that comes from
Thanks
x(x + 1)^3 - 42(x + 1)^2 = 0
x(x + 1)^3 = 42(x + 1)^2
x(x + 1) = 42
(x + 1/2)^2 = 169/4
x + 1/2 = +- 13/2
x = 6, x = -7
This is my work so far, and the book says I'm correct. However there is an additional answer x = -1, and I don't understand where that comes from
Thanks